Effect of buffer on fumarase reactions. (March 2016) - Dunford, H. Brian
Two specific mechanisms are proposed to explain the effect of buffer on the reactions catalysed by fumarase. In one mechanism, buffer catalyses a slow isomerisation of the enzyme in which a catalytic acid group on one side of the active site is replaced by another acid group on the opposite side. In the other mechanism the buffer-catalysed isomerisation reaction is fast. The latter mechanism fits the experimental data.